Cultos afro-brasileiros na Paraíba: uma história em construção (1940-2010) - Silva, Valdir de Lima (2011)
This thesis aims to contribute to a historical reconstruction of african-brazilian religions and afrrican-amerindian in Paraíba, namely: Jurema, Umbanda and Candomblé, respectively. The methodology of the study was basically the source of oral testimonies gathered through interviews with Mothers and Fathers-to-Saint, as well as with representatives of Federations african-brazilian. We also use various resources, primary sources, documents, laws, resources iconographic, photographic, etc. Through rich material published on the subject, we reconstructed, part of the history, demonstrating also tabulate some pictures. The use of the ancestral language, through pontos, prayers, corimas, is recurrent in the course of work, beyond the narrative of African myths in the same corpus. We made a historic reconstruction of the secular cult of the Jurema Preta, in the Site Acais, in Alhandras City , the traditional Catimbó Jurema, training Umbanda Paraibana, with the contribution of woman priests as Mother Rita Preta and Mother Laura of Santa Rita, Mother Marinalva and Father Osias of João Pessoa City. One of the most important research, takes place with the 3.434 Law, signed by Governor João Agripino (1966-1971), guaranteeing freedom of worship African-paraiba. The trajectory of militants as Mother Rita Preta, Mother Marinalva, Cícero Tomé and Carlos Leal Rodrigues (In Memorian) and had to arise on the first African-federation of Paraíba. Bellow, we recorded the arrival of traditional Candomblé the State of Paraíba, through Father Jackson of Oyá (Cajazeiras), Father Erivaldo d’Osum, both from the Ketu nation, Mother Beata of Yemonjá (In Memorian), the nation of Angola, and Mother Renilda of Alaketu (Jeje Savalú), both of João Pessoa, between the decades of 1960-1990. Finally we analyze the appearance and role o federations, usually created dissent.